Second Language Speaking Anxiety among TESL Undergraduates in a Private University - Achanan, Sri Aiswarrya; Ramuloo, Punitha; Mohamad, Ayu Rita (Selangor Humaniora Review, 2021)
English became the second language of Malaysia after independence. Thereby, fluency in speaking English has become essential, particularly for undergraduates studying Teaching English as a Second Language (TESL), as English is their medium of instruction. However, despite learning the language for several years, undergraduates experience anxiety when speaking English. Due to that reason, this study aims to examine the level of anxiety in speaking English as a second language and the causes of speaking anxiety in the English language among TESL undergraduates in a private university. This study uses the quantitative method to collect the data. The quantitative data was gathered through a questionnaire named (ELCAS) English Language Classroom Anxiety Scale with 23 items which were adopted and adapted from (FLCAS) Foreign Language Classroom Anxiety Scale. The data were examined using descriptive statistics in Statistical Package for the Social Science (SPSS). This research included 100 TESL undergraduates from a private university. The results revealed that a significant number of undergraduates had high-level anxiety in speaking English. The findings also discovered that the main cause of speaking anxiety is a lack of confidence among the TESL undergraduates. The undergraduates should learn how to overcome speaking anxiety by practicing speaking independently and not feeling inferior about themselves.